Improving Peer Feedback on Arguments - Goddiksen, Mads (Improving University Science Teaching and Learning, 2023)
Peer feedback can increase learning for both the person receiving feedback and, especially, the person providing (Nicol et al., 2013). Providing feedback on results of higher level cognition including evaluations and creative processes is what participants often find most challenging (UNSW, 2018). Clear and concrete guidelines should therefore be provided, if the peer feedback session is to be successful (Winstone and Carless, 2019, Ch 8). The aim of this study was therefore to test an intervention – in the form of guidelines - designed to improve the learning outcome of peer feedback sessions where participants had to provide feedback on complex arguments.